Solve the following simultaneous equations: y-3x+2=0, y^2-x-6x^2=0

(1) y-3x+2=0
(2) y2-x-6x2=0
Using (1): y=3x-2
Sub y value into (2): (3x-2)2-x-6x2=0
Expand the brackets: 9x2-13x+4-x-6x2=0
Group terms: 3x2-13x+4=0
Factorise: (3x-1)(x-4)=0
Find roots (set brackets equal to 0): 3x-1=0, x-4=0x=1/3, x=4
Sub into equation (1) to find y values: y=-1, y=10.

Answered by Phoebe A. Maths tutor

7183 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find ∫ (2x^5 - 1/(4x^3)-5) dx. giving each term in its simplest form.


Find the stationary points of y = (x-7)(x-3)^2.


Differentiate y=x^3ln2x


Why does the equation x^2+y^2=r^2 form a circle in the Cartesian plane?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences